Becoming Nisei : Japanese American Urban Lives in Prewar Tacoma - Hoffman, Lisa M. (Lisa Mae); Hanneman, Mary L. (Mary Louise) (Book collections on Project MUSE., 2021)
"As a key West Coast destination for Japanese immigration to the U.S., Tacoma's vibrant nihonmachi had a significant population of Issei and Nisei by the 1920s and 1930s. Prior to World War II, the Tacoma Japanese Language School served as a community hub for the Japanese American community in the city. Based on interviews with over 40 Nisei former students of the school, Lisa Hoffman and Mary Hanneman develop an interdisciplinary analysis of identity construction and negotiations over belonging by second generation Japanese Americans in pre-World War II urban America. With an approach both transnational in perspective and focused on urban space, the book explores the everyday lives of Japanese American children prior to incarceration, including the impact of their daily study at and participation in community events associated with the school. Drawing from interviews and archival sources, the authors illuminate the rich prewar cultural experiences of Japanese Americans in the city, a distinct social history often eclipsed by a focus on wartime incarceration. Additionally, the book underscores the role of the Japanese government and imperial Japanese educational traditions in shaping Tacoma's JLS, as Japan sought to emerge as an equal member of the international community."--